The Influence of Social Media on Tourists’ Visiting Decisions toward Nature-Based Tourism Destinations - Rani Vaniya Suwondo; Emily Carter; Michael Tan (Tourism and Hospitality Research, 2026)
The rapid growth of digital technology has transformed the tourism industry, particularly through the increasing influence of social media on tourists’ travel behavior and destination choices. This study aims to analyze the influence of social media on tourists’ visiting decisions toward nature-based tourism destinations. A quantitative research approach with a survey design was employed in this study. Data were collected from 250 domestic tourists who had visited nature-based tourism destinations in Indonesia during the last two years. The research instrument consisted of structured questionnaires using a five-point Likert scale. Data were analyzed using descriptive statistics and multiple linear regression analysis. The findings indicate that visual content, online reviews, and influencer recommendations significantly affect tourists’ destination image formation and visiting intentions. Social media platforms such as Instagram, TikTok, and YouTube play a crucial role in increasing destination visibility, emotional attachment, and tourists’ trust toward tourism destinations. Furthermore, user-generated content was identified as one of the strongest factors influencing tourists’ decision-making processes. The study also reveals that authentic digital communication and sustainable destination branding contribute positively to tourists’ satisfaction and revisit intention. This research contributes theoretically to tourism marketing literature by expanding the understanding of social media’s role in nature-based tourism. Practically, the findings provide important implications for destination managers and tourism stakeholders in developing effective and sustainable digital marketing strategies.